A Kantian Perspective on Individual Responsibility for Sustainability. Issue 1 (2nd January 2021) - Wallace, Kathleen
ABSTRACT: I suggest that the Kantian categorical imperative can be a basis for an ethical duty to live sustainably. The universalizability formulation of the categorical imperative should be seen as a test of whether the principle underlying a way of life is self-destructive of the system of living and acting which makes the way of life possible. In exploring this interpretation the self should be conceptualized as a socially and system-constituted being, rather than an atomized will. In this sense, a self which lives in a way that is destructive of the system of life, is also in principle willing its own self-destruction.